School Segregation and Racial Gaps in Special Education Identification - Elder, Todd E.; Figlio, David N.; Imberman, Scott A.; Persico, Claudia L. (Journal of Labor Economics, 2021)
We use linked birth and education records from Florida to investigate how the identification of childhood disabilities varies by race and school racial composition. Using a series of decompositions, we find that black and Hispanic students are identified with disabilities at lower rates than are observationally similar white students. Black and Hispanic students are overidentified in schools with relatively small shares of minorities and substantially underidentified in schools with large minority shares. Our results are consistent with a heightened awareness among school officials of disabilities in students who are racially and ethnically distinct from the majority race in the school.